Matrix remodeling-associated protein 5 as a novel biomarker for predicting disease activity and endoscopic response to infliximab in Crohn's disease - Daopo Lin; Jiayue Xu; Mengqian Ye; Luyan Fang; Tianhao Xia; Wenyu Tong; Gokuljayanth Jayaseelan Ranichandra; Yifan Bao; Bo Zheng; Yi Jiang; Lianpin Wu; Dingyuan Hu (Journal of Translational Autoimmunity)
The primary objective of treating Crohn's disease (CD) is to achieve and sustain endoscopic remission. However, repeated endoscopic examination leads to decreased patient compliance and procedural risks. Non-invasive biomarkers for endoscopic activity of CD are thus promising in clinical use. This study compared proteomic profiles between inflammatory and non-inflammatory intestinal tissues on 10 active CD patients through liquid chromatography–tandem mass spectrometry, and identified 384 differentially expressed proteins. Four candidate secretory proteins (MXRA5, AZU/HBP, CRYAB, DEFA3) were validated via ELISA in serum from 74 CD patients (43 active CD and 31 in remission). Serum MXRA5 levels were notably increased in CD patients in remission compared to active cases (P < 0.001) and showed an inverse correlation with SES-CD scores (r = −0.33, P < 0.05). ROC analysis demonstrated MXRA5's utility in distinguishing endoscopic activity of patients with CD (AUC = 0.80), which was improved when combined with CRP (AUC = 0.89). Besides, higher baseline serum MXRA5 levels predicted better endoscopic response to infliximab (IFX). In conclusion, our study indicates that MXRA5 might serve as a new potential serum biomarker for CD activity and IFX response prediction. Further prospective and muli-center studies are needed to validate its predictive performance.